Innovating employee participation in the Netherlands; Innovationen in der Beschaf̈tigtenpartizipation in den Niederlanden - Frank Tros (Industrielle Beziehungen, 2022)
In this article, thirteen case studies are analysed which study the innovation processes renewing structures and forms of employee participation in companies in private and public sectors of industry in the Netherlands. In the majority of the case studies, new hybrid forms between representative and direct participation have been launched, in which elected members of works councils co-operate with non-member employees, mostly in temporary projects. These initiatives show successful results in mobilizing employee involvement in representative as well as in direct workers' participation, and in improving efficiency and effectiveness in consultations with management in the workplace, as well as with company directors. At the same time, however, works councils have compromised on lowering the number of seats on their councils, leading to dilemmas around questions of democracy, formal powers and coordination. Furthermore, these experiments show limitations in their scope. Firstly, they hardly address more effective inclusion of the many (younger) workers with flexible contracts in employee participation schemes, nor the broader potential impacts on companies' strategic decision-making. It can be concluded that practices aimed at renewing employee participation develop within the confines of the traditional characteristics of Dutch industrial relations, such as cooperative relationships between works councils and management, a low level of interventions from trade unions and a focus on the field of operational management (rather than on conflictual workers interests and strategic issues). – – In diesem Beitrag werden 13 Fallstudien analysiert, die Innovationsprozesse untersuchen, die zur Erneuerung von Strukturen und Formen der Beschaf̈tigtenpartizipation im privaten und of̈fentlichen Sektor der Niederlande gefuḧrt haben. Die Mehrzahl der Fallstudien betrifft neue, repras̈entative und direkte Partizipation kombinierende Mischformen, bei denen gewaḧlte Betriebsratsmitglieder - zumeist im Rahmen befristeter Projekte - mit nicht dem Betriebsrat angehor̈enden Beschaf̈tigten kooperieren. An diesen Initiativen ist zu sehen, dass es nicht nur gelingt, Beschaf̈tigte sowohl fur̈ die repras̈entative als auch fur̈ die direkte Partizipation zu gewinnen, sondern auch, die Konsultationen auf Betriebs- und Unternehmensebene effizienter und effektiver zu gestalten. Allerdings haben sich die Betriebsraẗe auf eine Reduzierung der Anzahl der Betriebsratssitze eingelassen, was Fragen in Bezug auf die demokratische Legitimation, formale Rechte und die Koordination aufwirft. Auch ist zu erkennen, dass diese Experimente nur eine bedingte Reichweite besitzen: Zum einen gelingt es kaum, die vielen ( jun̈geren) Arbeitskraf̈te mit flexiblen Arbeitsvertrag̈en wirksam einzubeziehen; zum anderen werden damit auch die weitergehenden potenziellen Auswirkungen strategischer Unternehmensentscheidungen nicht erfasst. Die auf die Erneuerung der Mitarbeiterpartizipation abzielenden Praktiken entwickeln sich, wie zu sehen ist, innerhalb des traditionellen niederlan̈dischen Systems der Arbeitsbeziehungen - geprag̈t durch ein kooperatives Verhal̈tnis zwischen Betriebsraẗen und Betriebsleitung, ein geringes Maß an Intervention von gewerkschaftlicher Seite und mit Fokus auf operativen betrieblichen Ablaüfen und nicht auf konfliktive Arbeitnehmerinteressen und Strategiefragen.Schlagworte: Betriebsraẗe, organisatorischer Wandel, Beschaf̈tigtenpartizipation, Mitbestimmung.
Keywords: J50; J53; J83; 330; Works councils; organisational change; employee participation; co determination